Associations between television viewing and physical activity and low back pain in community-based adults: A cohort study. Issue 25 (June 2016) - Hussain, Sultana Monira; Urquhart, Donna M.; Wang, Yuanyuan; Dunstan, David; Shaw, Jonathan E.; Magliano, Dianna J.; Wluka, Anita E.; Cicuttini, Flavia M.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Two systematic reviews concluded that there was limited evidence to support an association between physical activity and sedentary behavior and developing low back pain (LBP). The aim of this study was to examine the associations of physical activity and television viewing time with LBP intensity and disability in community-based adults. Five thousand fifty-eight participants (44% men) of the Australian Diabetes, Obesity and Lifestyle Study had physical activity and television viewing time measured in 1999 to 2000, 2004 to 2005, and 2011 to 2012, and LBP intensity and disability assessed in 2013 to 2014 using the Chronic Pain Grade Questionnaire. Multinomial logistic regressions were used to estimate the odds ratio for LBP intensity and disability associated with physical activity and television viewing time. Analyses were adjusted for age, education, smoking, dietary guideline index score, body mass index, and mental component summary score. To test whether associations of physical activity or television viewing time with LBP intensity and disability were modified by sex, obesity, or age, interactions were tested using the likelihood ratio test. As gender modified the associations between physical activity and television viewing time and LBP disability ( P = 0.05), men and women were examined separately. A total of 81.7% men and 82.1% women had LBP. Most men (63.6%) and women (60.2%) had low intensity LBP with fewer having high intensity LBP (18.1% men, 21.5% women). Most participants had no LBP disability (74.5% men, 71.8% women) with the remainder reporting low (15.8% men, 15.3% women) or high (9.7% men, 12.9% women) LBP disability. Insufficient physical activity (<2.5 hours/week) was not associated with LBP intensity or disability. High television viewing time (≥2 hours/day) was associated with greater prevalence of LBP disability in women (low disability OR 1.35, 95% CI 1.04–1.73; high disability OR 1.29, 95% CI 1.01–1.72). Although it needs to be confirmed in RCTs our findings suggest that targeting time spent watching television and possibly other prolonged sedentary behaviors may have the potential to reduce LBP disability in community-based adults, particularly in women.